Association Between Diet Quality and Risk of Ovarian and Endometrial Cancers: A Systematic Review of Epidemiological Studies - Zhang, Yu-Hua; Li, Zhuo; Tan, Ming-Zi (Frontiers in Oncology, 2021)
Abstract Objectives The relationship between diet quality indices and risk of ovarian and endometrial cancers were unclear. We aimed at conducting a systematic review to evaluate the epidemiological evidence. Methods Embase, PubMed, Web of Science and Scopus databases were searched for eligible studies up to December 2020. Epidemiological studies reported the association of the diet quality with risk of ovarian and endometrial cancers were evaluated. Results Eleven eligible studies were identified, of which six studies were case-control studies, four were cohort studies, and one was case-cohort study. All studies were considered as high-quality with low risk of bias. Seven studies evaluated the association of diet quality with risk of ovarian cancer. Four studies reported null association for diet quality indices such as Healthy Eating Index (HEI)-2005, HEI-2010, Mediterranean Diet Score (MDS) and Recommended Foods Score (RFS). Two studies reported significantly inverse association for Alternate Healthy Eating Index (AHEI)-2010 and Healthy Diet Score (HDS) indices. One study reported significantly increased risk of ovarian cancer associated with higher level of Dietary Guidelines for Americans Index. Dose-response analysis showed pooled relative risks of 0.98 (95%Cl: 0.95, 1.01) and 0.94 (95%Cl: 0.77, 1.13) for each 10 points increase in the HEI-2005 and AHEI-2010 indices. Seven studies evaluated the association of diet quality with risk of endometrial cancer. Three studies reported significantly inverse association of diet quality as assessed by the MDS and Diet Score Quintiles with risk of endometrial cancer. Four studies reported null association for other diet quality indices including HEI-2005, HEI-2010, RFS and HDS. Dose-response analysis showed a pooled relative risk of 0.87 (95%CI: 0.81, 0.93) for one unit increment of the MDS. Conclusion This study suggests little evidence on the association between diet quality and risk of ovarian cancer. Adherence to high quality diet, as assessed by MDS, might be associated with lower the risk of endometrial cancer.